2022
DOI: 10.1093/jn/nxac075
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Marine Oil Supplement Increases Specific Plasma Specialized Pro-Resolving Mediators in Adults with Obesity

Abstract: Background Specialized pro-resolving mediators (SPM), synthesized from polyunsaturated fatty acids (PUFA), resolve inflammation and return damaged tissue to homeostasis. Thus, increasing metabolites of the SPM biosynthetic pathway may have potential health benefits for select clinical populations such as those with obesity that display dysregulation of SPM metabolism. However, bioavailability of SPMs and their metabolic intermediates in humans with obesity remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Due to the elevated risk of mortality with these diseases, there is a need for strategies in its identification, prevention, and treatment within healthcare. In 2022, as evidenced in Figure 5, the bulk of research articles focussed on related diseases: CVD, 232–255 diabetes, 166,233,249,250,256–278 liver disease, 51,279–293 MetS 277,294,295 and obesity 277,295–305 …”
Section: In Review: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the elevated risk of mortality with these diseases, there is a need for strategies in its identification, prevention, and treatment within healthcare. In 2022, as evidenced in Figure 5, the bulk of research articles focussed on related diseases: CVD, 232–255 diabetes, 166,233,249,250,256–278 liver disease, 51,279–293 MetS 277,294,295 and obesity 277,295–305 …”
Section: In Review: Results and Discussionmentioning
confidence: 99%
“…Bibliometric analyses of clinical lipidomics publications in 2022 according to separation techniques, detectors, and RPLC columns used …”
Section: In Review: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most well studied causes of variation is diet, particularly the effects of differing dietary fatty acids since oxylipins are derived from PUFAs. In the past 18 months reports on the effect of diet in healthy children at risk for type 1 diabetes [38] and on the effects of fish oil supplementation in healthy young adults [11], adults with migraines [39], and in adults with obesity [40,41] have confirmed previous findings (reviewed [6]) that higher dietary/supplemental eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) result in higher plasma EPA and DHA oxylipins, while effects on ARA-derived oxylipins are more heterogeneous. In healthy young adults, changes can be observed 1 day after initiation of supplementation with a DHA-rich fish oil, and EPA and DHA oxylipins reach a plateau by 1 week of supplementation [11].…”
Section: Biological Variation Of Oxylipins -Diet and Healthmentioning
confidence: 99%
“…inflammation resolution and tissue repair). Recent studies from many independent investigators have linked alterations in the endogenous production of these molecules with disease propagation and severity [1][2][3][4] as well as with the protective activities of omega-3 supplements [5][6][7] . Studies by Gilroy and colleagues have indicated how efficient engagement of SPM, namely 15-epi-lipoxin A4, links with the ability of humans to resolve inflammation as well as to respond to the anti-inflammatory activities of aspirin 8,9 .…”
mentioning
confidence: 99%